Inversión pública, crecimiento económico y desigualdad en la Región La Libertad, 2000 - 2015 - Cruzado Pérez, Daniel Alexander (2016)
This thesis focuses on the importance of the study of development at the regional level, with the main purpose of analyzing and defining how public investment relates to economic growth and inequality in the La Libertad region for the 2000 period - 2015. The hypothesis around which this work revolved was that public investment is directly related to economic growth and inversely with inequality in the La Libertad region, in the period 2000-2015. This research takes the annual data of Public Investment, GDP per capita and Gini Coefficient, to describe the evolution of each variable in La Libertad for the period covered by the present. It analyzes and defines, from the data collected and ordered, the evolution of the public investment in the region, the trend that it takes throughout the period and the sectors in which it was most invested, besides describing the participation of each level of Government in this regard. In the same way, it performs the data analysis to define the Economic Growth that has taken place in La Libertad for the study period, describing the evolution of GDP per capita and the most productive sectors that comprise the economic activity in the region. In parallel, it analyzes and defines Economic Inequality in La Libertad for the same period, studying the evolution of the Gini Coefficient. It applies two simple linear regression models to determine the relation, in the first instance, between Public Investment and Economic Growth, and secondly, the relationship between this Public Investment and Economic Inequality in the region of La Libertad between 2000 - 2015. The central result of the present study is the confirmation of the hypothesis proposed, as it demonstrates the direct relationship between Public Investment and Growth, and the inverse relationship between Investment and Inequality.